Pengaruh Budaya Organisasi, Peran Auditor Internal, Peran Auditor Eksternal, Dan Internal Control Terhadap Pencegahan Fraud Di Jakarta - Jessica Novia, Susanto Salim (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
This study has a purpose, namely to prove the impact or influence of organizational culture, the role of internal auditors, the role of external auditors, and internal control on prevention of fraud. This study uses primary data. This research selected data with purposive sampling technique. This research was conducted on people who work in accounting and finance, namely finance directors, financial managers, accounting managers, financial supervisors / assistants, accounting supervisors / assistants, financial staff, and accounting staff who work in companies located in Jakarta. The entire sample used in this study was 60 respondents. Research data is processed using SPSS Statistics Version 23. The results of this study indicate that the role of internal auditors and the role of external auditors have a positive and not significant influence to fraud prevention. Organizational culture and internal control have a positive and significant influence to prevention of fraud